Verbal and Nonverbal Factors Influencing the Success of Da’wah Communication By Ustadz Abdul Somad - Qarni, Waizul; Syahnan, Mhd.; Harahap, Isnaini; Nasution, Sahkholid; Fithriani, Rahmah (KnE Social Sciences, 2019)
Da’wah is the term used to refer to the process of spreading information about Islam by a da’I (a Muslim communicator). Indonesia, as the country with the biggest Muslim population in the world has produced a large number of da’I who gain popularity in either, local, national, or international scale. Ustadz Abdul Somad is one among the most popular da’I from Indonesia who in the last few years has attracted audience across various social economic, educational, and political backgrounds. Driven by the popularity gained by Abdul Somad which outruns most other da’I in Indonesia, this study aims to investigate the factors influencing the success of his da’wah communication. This study applied a descriptive qualitative approach using documentation and interview as the instruments of data collection. The findings show that there are two main factors behind the success of his da’wah communication, First, the verbal factors which include comprehensive reference and the language choice. Second, the nonverbal one, which in this case is the use of various platforms for da’wah dissemination. Keywords: Communication, Da’wah, Verbal, Nonverbal